The Effect of Visual Feedback on Knee Pain and Function in Women Aged 45–75 Following Total Knee Arthroplasty - Sandra Baltramonaitytė; Anelė Katinė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Knee replacement surgery is a standard treatment that relieves the problems caused by advanced knee osteoarthritis. Postoperative rehabilitation programs are extremely important because they can improve knee function and reduce pain in patients after EP surgery.